The Wender Cedrene Synthesis Revisited: A Catalytic Enantioselective Entry to the Chiral Key Intermediate - Westphal, Julia; Schumacher, Christian Eric; Schmalz, Hans-Günther (Synthesis, 2017)
The seminal synthesis of the sesquiterpene (±)-α-cedrene reported by Wender in 1981 offers a uniquely short and elegant access to the bridged-tricyclic target compound by exploiting an intramolecular arene-olefin photocycloaddition. However, the synthesis was performed only in the racemic series so far. This synthesis was now re-investigated and the catalytic methods for the enantioselective preparation of the chiral key intermediate were evaluated. It was found that Cu-catalyzed allylic substitution of a cinnamyl chloride with MeMgBr in the presence of a Taddol-derived chiral phosphine-phosphite ligand affords the corresponding (1-methylallyl)arene with high enantioselectivity (94% ee). Hydroboration and subsequent Suzuki coupling gave (R)-curcuphenol methyl ether from which (–)-α-cedrene was prepared along the route paved by Wender.
Keywords: terpenoids; total synthesis; enantioselectivity; asymmetric catalysis; allylation; photochemistry; copper; chiral P,P-ligands